Nano cellulose glass anti-mildew paper and production process thereof
By adding modified nanocellulose, compound anti-mold agent and waterproof coating to the production process of glass spacer paper, the existing glass spacer paper has been solved, and the mildew and waterproof performance is insufficient, achieving more efficient anti-mold and waterproof effects, extending service life and improving paper quality.
Patent Information
- Application Number
- CN202411899422.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
The existing glass spacer paper has poor mildew resistance and waterproof performance, resulting in shortened service life and poor quality.
Using the production process of nanocellulose glass anti-mold paper, paper with excellent anti-mold and waterproof properties is prepared by combining modified nanocellulose, compound anti-mold agents and waterproof coatings with bleached coniferous wood pulp and broad-leaf wood pulp.
It significantly improves the anti-mold and waterproof properties of nanocellulose glass anti-mold paper, extends its service life, and ensures its quality and quality.
Smart Images

Figure BDA0005202748880000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of papermaking, in particular to a nano-cellulose glass mildew-proof paper and a production process thereof. Background Art
[0002] Cellophane is a kind of paper used to protect glass from adhesion and scratches. It has specific applications in the glass deep processing industry. It is mainly used to protect flat glass during production, transportation and installation to prevent direct contact and adhesion between glass plates, thereby preventing the glass from being scratched or contaminated. In the patent document with application number "CN202111279432.7", a glass spacer paper and a preparation method are disclosed, wherein the glass spacer paper includes 50-70% of native hardwood pulp, 25-40% of native softwood pulp, 10-15% of starch, 3-10% of nanofiber reinforcement and 1-5% of pH regulator. Although the glass spacer paper prepared in this patent document can play a good protective role on the glass surface and reduce the chance of glass being scratched during transportation. However, its own mildew resistance is relatively poor, which shortens its service life to a certain extent. Furthermore, its own waterproof performance is relatively insufficient, which affects its quality to a certain extent. Therefore, the present invention provides a nanocellulose glass mildew-proof paper and a production process thereof to solve the above-mentioned technical problems. Summary of the invention
[0003] The purpose of the present invention is to provide a nanocellulose glass mildew-proof paper and a production process thereof. The prepared nanocellulose glass mildew-proof paper not only has good mildew-proof performance, but also has excellent waterproof performance, which prolongs its service life to a certain extent while also ensuring its quality.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] In a first aspect, the present invention provides a production process of nanocellulose glass mildew-proof paper, comprising the following steps:
[0006] The first step is to perform pulping treatment on bleached coniferous wood pulp and bleached broadleaf wood pulp respectively, and then, according to the absolute dry weight percentage, 30-50% of bleached coniferous wood pulp and 50-70% of bleached broadleaf wood pulp are mixed evenly, and the composite wood pulp is pre-acidified for 20-30 minutes; after the acidification is completed, the pH of the composite wood pulp is adjusted to 5.5-6.0 to obtain a mixed pulp; wherein the beating degree of the bleached coniferous wood pulp and the bleached broadleaf wood pulp are both 40-60°SR;
[0007] The second step is to sequentially add the modified nanocellulose aqueous dispersion, compound mildewproof agent, sizing agent and retention aid to the mixed slurry, mix and stir evenly, and then put it on the net to make a wet paper web, and then squeeze and dehydrate the wet paper web by continuous light pressing to ensure that the dryness of the paper is 35-45%; wherein the concentration of the modified nanocellulose in the modified nanocellulose aqueous dispersion is 3-5wt%; and its dosage is 10-20% of the volume of the mixed slurry;
[0008] Step 3: Dry the paper obtained after pressing and dehydration at a temperature of 105-110°C. After drying, press 2-6 g / m 2 A waterproof coating is applied on the surface with a coating amount of , and then the nanocellulose glass mildew-proof paper is obtained after secondary drying, calendering, static elimination and winding treatment.
[0009] Furthermore, the preparation method of the compound mildew inhibitor comprises the following steps:
[0010] Step 1, ultrasonically disperse the inorganic carrier in an ethanol aqueous solution with a volume concentration of 70-85% at a solid-liquid ratio of 30-80 g / L, then add a silane coupling agent with a volume of 5-10% of the ethanol aqueous solution, and stir the reaction at a temperature of 50-65° C. for 5-8 hours after ultrasonic dispersion for 10-20 minutes; after the reaction is completed, the resulting components are sequentially subjected to solid-liquid separation, alcohol washing and vacuum drying to obtain a pretreated inorganic carrier;
[0011] Step 2: ultrasonically disperse the pretreated inorganic carrier in a mixed solution with a mass of 5 to 10 times that of the pretreated inorganic carrier, and then add 4-allyl-2-methoxyphenol with a mass of 0.8 to 1.2 times that of the pretreated inorganic carrier and 2,2-dimethoxy-2-phenylacetophenone with a mass of 0.05 to 0.08 times that of the pretreated inorganic carrier. After mixing evenly, stir and react under ultraviolet light for 6 to 10 hours. After the reaction is completed, filter, wash and dry the product components in turn, and the final product is a compound mildew inhibitor.
[0012] Furthermore, the preparation method of the inorganic carrier is: zinc acetate is dissolved in ethylene glycol at a dosage ratio of 20 to 50 g / L, and then ammonium acetate with a mass of 2 to 4 times that of zinc acetate and sodium citrate with a mass of 1 to 2 times that of zinc acetate are added thereto, and after stirring evenly, the resulting mixed components are transferred into a reaction device, and kept warm for reaction at a temperature of 170 to 200° C. for 15 to 20 hours; after the reaction is completed, the reaction product is naturally cooled to room temperature, and after filtering, the filter cake is washed alternately with ethanol and deionized water for 3 to 4 times, and then dried to obtain the inorganic carrier.
[0013] Furthermore, the preparation method of the mixed liquid is: N, N-dimethylformamide and deionized water are mixed in a volume ratio of 2 to 3:1, and then 3 to 6% by mass of isothiazolinone and 5 to 8% by mass of dodecyltrimethylammonium chloride are added to the obtained mixed solvent, and the mixed liquid is obtained after mixing and dispersing evenly.
[0014] Furthermore, the silane coupling agent is selected from any one of 2-mercaptopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 2-mercaptopropyltriethoxysilane and 3-mercaptopropyltriethoxysilane.
[0015] Furthermore, the preparation method of the modified nanocellulose is as follows: adding nanocellulose at a dosage ratio of 0.02 to 0.05 g / mL into a 70 to 80 wt% ethanol aqueous solution, adding methyltrimethoxysilane in an amount of 0.3 to 0.4 times the mass of the nanocellulose after ultrasonic dispersion, mixing and stirring evenly, and then standing to react for 3 to 5 hours; after the reaction is completed, filtering and drying the reaction products in turn, and the obtained product is the modified nanocellulose.
[0016] Furthermore, the sizing agent is selected from any one of oxidized starch, polyvinyl alcohol, and vinyl acetate maleic anhydride copolymer, and its usage is 2-4% of the dry weight of the paper.
[0017] Furthermore, the retention aid is selected from any one of melamine formaldehyde resin, propylene oxide or cationic starch, and its usage is 0.8-2% of the dry weight of the paper.
[0018] Furthermore, the waterproof coating is composed of the following raw materials in parts by weight: 40 to 50 parts of polyurethane resin emulsion, 25 to 35 parts of acrylic resin emulsion, 10 to 15 parts of zirconium phosphate, 8 to 12 parts of mica powder, 2 to 3 parts of polyoxyethylene polyoxypropylene pentaerythritol ether, 3 to 5 parts of nano cerium oxide, 2 to 3 parts of propylene glycol methyl ether acetate and 1.5 to 2.5 parts of dispersant.
[0019] In a second aspect, the present invention provides a nanocellulose glass mildew-proof paper, which is produced using the production process described above.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The invention uses zinc acetate, ammonium acetate and sodium citrate as raw materials to prepare nano zinc oxide with a porous structure, namely an inorganic carrier. Then, the inorganic carrier is put into an ethanol aqueous solution and a silane coupling agent is added, and the two are bonded through a chemical reaction through stirring reaction to obtain a pre-treated inorganic carrier. Then, the pre-treated inorganic carrier is ultrasonically dispersed in a mixed solution, and during the ultrasonic dispersion, isothiazolinone and dodecyltrimethylammonium chloride in the mixed solution are uniformly adsorbed and reside on the surface of the inorganic carrier and inside its porous structure. Then, under the action of 2,2-dimethoxy-2-phenylacetophenone, 4-allyl-2-methoxyphenol is effectively grafted on the surface of the inorganic carrier and inside its porous structure, so that isothiazolinone and dodecyltrimethylammonium chloride are fixed and encapsulated, and the probability of migration of isothiazolinone and dodecyltrimethylammonium chloride is reduced. Finally, under the synergistic cooperation of inorganic carrier, isothiazolinone and dodecyltrimethylammonium chloride, the prepared compound mildew-proof agent has excellent antibacterial and mildew-proof properties, and the use of the compound mildew-proof agent as a raw material of nanocellulose glass mildew-proof paper can significantly improve its mildew-proof properties and extend its service life to a certain extent. Furthermore, the nanocellulose glass mildew-proof paper prepared by the present invention also has excellent waterproof properties, which effectively guarantees its quality. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] A production process of nanocellulose glass mildew-proof paper comprises the following steps:
[0025] The first step is to perform pulping treatment on bleached coniferous wood pulp and bleached broadleaf wood pulp respectively, and then, according to the absolute dry weight percentage, 30% of bleached coniferous wood pulp and 70% of bleached broadleaf wood pulp are mixed evenly, and the composite wood pulp is pre-acidified for 20 minutes; after the acidification is completed, the pH of the composite wood pulp is adjusted to 5.5 to obtain a mixed pulp; wherein the beating degree of the bleached coniferous wood pulp and the bleached broadleaf wood pulp is 40°SR; the pH regulator used for the pre-acidification treatment and the pH adjustment is a citric acid aqueous solution with a concentration of 2 to 5wt%;
[0026] Step 2: Add modified nanocellulose aqueous dispersion, compound mildewproof agent, sizing agent and retention aid to the mixed slurry in sequence, mix and stir evenly, and then put it on the net to make wet paper web, and then squeeze and dehydrate the wet paper web by continuous light pressing to ensure that the dryness of the paper is 35%;
[0027] The concentration of modified nanocellulose in the modified nanocellulose aqueous dispersion is 3wt%; and its dosage is 10% of the volume of the mixed slurry; polyvinyl alcohol is selected as the sizing agent, and its dosage is 2% of the dry weight of the paper; melamine formaldehyde resin is selected as the retention agent, and its dosage is 0.8% of the dry weight of the paper;
[0028] The preparation method of modified nanocellulose is as follows: adding nanocellulose to a 70wt% ethanol aqueous solution at a dosage ratio of 0.02g / mL, uniformly dispersing by ultrasonication, adding methyltrimethoxysilane in an amount of 0.3 times the mass of nanocellulose, mixing and stirring uniformly, and then standing for reaction for 3h; after the reaction is completed, filtering and drying the reaction products in turn, and the obtained product is the modified nanocellulose;
[0029] Step 3: Dry the paper obtained after pressing and dehydration at a temperature of 105°C. After drying, press 2g / m 2 The waterproof coating is coated on the surface with a coating amount of , and then the nanocellulose glass mildew-proof paper is obtained after secondary drying, calendering, static elimination and winding treatment in sequence;
[0030] The waterproof coating is composed of the following raw materials in parts by weight: 40 parts of polyurethane resin emulsion, 25 parts of acrylic resin emulsion, 10 parts of zirconium phosphate, 8 parts of mica powder, 2 parts of polyoxyethylene polyoxypropylene pentaerythritol ether, 3 parts of nano cerium oxide, 2 parts of propylene glycol methyl ether acetate and 1.5 parts of dispersant;
[0031] The polyurethane resin emulsion was purchased from Shenzhen Yoshida Chemical Co., Ltd. and sold the water-based polyurethane resin emulsion model F0403;
[0032] The acrylic resin emulsion was purchased from Dongguan Baihong Environmental Protection Technology Co., Ltd. and sold under the brand name BH-S353.
[0033] The dispersant was purchased from Foshan Hongchang New Materials Co., Ltd. and was a transparent, colorless, aqueous dispersant with model number W-4006.
[0034] The preparation method of the compound mildew inhibitor comprises the following steps:
[0035] Step 1, ultrasonically disperse the inorganic carrier in an ethanol aqueous solution with a volume concentration of 70% at a solid-liquid ratio of 30g / L, then add 2-mercaptopropyltrimethoxysilane with a volume of 5% of the ethanol aqueous solution, and stir the mixture at a temperature of 50°C for 5h after ultrasonic dispersion for 10min; after the reaction is completed, the obtained product components are sequentially subjected to solid-liquid separation, alcohol washing and vacuum drying to obtain a pretreated inorganic carrier;
[0036] Step 2: ultrasonically disperse the pretreated inorganic carrier in a mixed solution 5 times its mass, then add 4-allyl-2-methoxyphenol 0.8 times the mass of the pretreated inorganic carrier and 2,2-dimethoxy-2-phenylacetophenone 0.05 times the mass of the pretreated inorganic carrier, mix well and stir to react for 6 hours under ultraviolet light; after the reaction is completed, filter, wash and dry the product components in turn, and finally obtain a compound mildew inhibitor; wherein, the preparation method of the mixed solution is: mix N,N-dimethylformamide and deionized water in a volume ratio of 2:1, and then add 3% of isothiazolinone and 5% of dodecyltrimethylammonium chloride to the obtained mixed solvent, and mix and disperse evenly to obtain a mixed solution.
[0037] The preparation method of the inorganic carrier is as follows: zinc acetate is dissolved in ethylene glycol at a dosage ratio of 20 g / L, and then ammonium acetate with a mass of 2 times that of zinc acetate and sodium citrate with a mass of 1 times that of zinc acetate are added thereto, and after stirring evenly, the resulting mixed components are transferred into a reaction device, and kept warm for reaction at a temperature of 170° C. for 15 hours; after the reaction is completed, the reaction product is naturally cooled to room temperature, and after filtering, the filter cake is washed alternately with ethanol and deionized water for 3 times, and then dried to obtain the inorganic carrier.
[0038] Example 2
[0039] A production process of nanocellulose glass mildew-proof paper comprises the following steps:
[0040] The first step is to perform pulping treatment on the bleached coniferous wood pulp and the bleached broadleaf wood pulp respectively, and then, according to the absolute dry weight percentage, 40% of the bleached coniferous wood pulp and 60% of the bleached broadleaf wood pulp are mixed evenly, and the composite wood pulp is pre-acidified for 25 minutes; after the acidification is completed, the pH of the composite wood pulp is adjusted to 5.5 to obtain a mixed pulp; wherein the beating degree of the bleached coniferous wood pulp and the bleached broadleaf wood pulp is 50°SR;
[0041] Step 2: Add modified nanocellulose aqueous dispersion, compound mildewproof agent, sizing agent and retention aid to the mixed slurry in sequence, mix and stir evenly, and then put it on the net to make wet paper web, and then squeeze and dehydrate the wet paper web by continuous light pressing to ensure that the dryness of the paper is 40%;
[0042] The concentration of modified nanocellulose in the modified nanocellulose aqueous dispersion is 5wt%; and its dosage is 15% of the volume of the mixed slurry; polyvinyl alcohol is selected as the sizing agent, and its dosage is 3% of the dry weight of the paper; melamine formaldehyde resin is selected as the retention agent, and its dosage is 1.5% of the dry weight of the paper;
[0043] The preparation method of modified nanocellulose is as follows: adding nanocellulose to a 75wt% ethanol aqueous solution at a dosage ratio of 0.03g / mL, adding methyltrimethoxysilane in an amount of 0.3 times the mass of nanocellulose after ultrasonic dispersion, mixing and stirring evenly, and then standing for reaction for 4h; after the reaction is completed, filtering and drying the reaction products in turn, and the obtained product is modified nanocellulose;
[0044] Step 3: Dry the paper obtained after pressing and dehydration at a temperature of 110°C. After drying, press 5g / m 2 A waterproof coating is applied on the surface with a coating amount of , and then the nanocellulose glass mildew-proof paper is obtained after secondary drying, calendering, static elimination and winding treatments.
[0045] The preparation method of the compound mildew inhibitor comprises the following steps:
[0046] Step 1, ultrasonically disperse the inorganic carrier in an ethanol aqueous solution with a volume concentration of 80% at a solid-liquid ratio of 50g / L, then add 3-mercaptopropyltrimethoxysilane with a volume of 6% of the ethanol aqueous solution, and stir the reaction at a temperature of 60°C for 6h after ultrasonic dispersion for 15min; after the reaction is completed, the obtained product components are sequentially subjected to solid-liquid separation, alcohol washing and vacuum drying to obtain a pretreated inorganic carrier;
[0047] Step 2: Ultrasonic disperse the pretreated inorganic carrier in a mixed solution with a mass of 8 times that of the pretreated inorganic carrier, then add 4-allyl-2-methoxyphenol with a mass of 1 times that of the pretreated inorganic carrier and 0.06 times that of 2,2-dimethoxy-2-phenylacetophenone, mix well, and stir to react for 8 hours under ultraviolet light; after the reaction is completed, filter, wash and dry the product components in turn, and finally obtain a compound mildew inhibitor; wherein, the preparation method of the mixed solution is: mix N,N-dimethylformamide and deionized water in a volume ratio of 3:1, and then add 5% of isothiazolinone and 6% of dodecyltrimethylammonium chloride to the obtained mixed solvent, and mix and disperse evenly to obtain a mixed solution.
[0048] The preparation method of the inorganic carrier is as follows: zinc acetate is dissolved in ethylene glycol at a dosage ratio of 30 g / L, and then ammonium acetate 3 times the mass of zinc acetate and sodium citrate 1.5 times the mass of zinc acetate are added thereto, and after stirring evenly, the resulting mixed components are transferred into a reaction device, and kept warm for reaction at a temperature of 180°C for 15 hours; after the reaction is completed, the reaction product is naturally cooled to room temperature, and after filtering, the filter cake is washed alternately with ethanol and deionized water for 3 times, and then dried to obtain the inorganic carrier.
[0049] Example 3
[0050] A production process of nanocellulose glass mildew-proof paper comprises the following steps:
[0051] The first step is to perform pulping treatment on the bleached coniferous wood pulp and the bleached broadleaf wood pulp respectively, and then, according to the absolute dry weight percentage, 50% of the bleached coniferous wood pulp and 50% of the bleached broadleaf wood pulp are mixed evenly, and the composite wood pulp is pre-acidified for 30 minutes; after the acidification is completed, the pH of the composite wood pulp is adjusted to 6.0 to obtain a mixed pulp; wherein the beating degree of the bleached coniferous wood pulp and the bleached broadleaf wood pulp is 60°SR;
[0052] Step 2: Add modified nanocellulose aqueous dispersion, compound mildewproof agent, sizing agent and retention aid to the mixed slurry in sequence, mix and stir evenly, and then put it on the net to make wet paper web, and then squeeze and dehydrate the wet paper web by continuous light pressing to ensure that the dryness of the paper is 45%;
[0053] The concentration of modified nanocellulose in the modified nanocellulose aqueous dispersion is 5wt%; and its dosage is 20% of the volume of the mixed slurry; polyvinyl alcohol is selected as the sizing agent, and its dosage is 4% of the dry weight of the paper; melamine formaldehyde resin is selected as the retention agent, and its dosage is 2% of the dry weight of the paper;
[0054] The preparation method of modified nanocellulose is as follows: adding nanocellulose to an 80wt% ethanol aqueous solution at a dosage ratio of 0.05g / mL, uniformly dispersing by ultrasonication, adding methyltrimethoxysilane in an amount of 0.4 times the mass of nanocellulose, mixing and stirring uniformly, and then standing for reaction for 5h; after the reaction is completed, filtering and drying the reaction products in turn, and the obtained product is the modified nanocellulose;
[0055] Step 3: Dry the paper obtained after pressing and dehydration at a temperature of 110°C. After drying, press 6g / m 2 A waterproof coating is applied on the surface with a coating amount of , and then the nanocellulose glass mildew-proof paper is obtained after secondary drying, calendering, static elimination and winding treatment.
[0056] The preparation method of the compound mildew inhibitor comprises the following steps:
[0057] Step 1, ultrasonically disperse the inorganic carrier in an ethanol aqueous solution with a volume concentration of 85% at a solid-liquid ratio of 80g / L, then add 2-mercaptopropyltriethoxysilane with a volume of 10% of the ethanol aqueous solution, and stir the mixture at a temperature of 65°C for 8h after ultrasonic dispersion for 20min; after the reaction is completed, the obtained product components are sequentially subjected to solid-liquid separation, alcohol washing and vacuum drying to obtain a pretreated inorganic carrier;
[0058] Step 2: Ultrasonic disperse the pretreated inorganic carrier in a mixed solution with a mass 10 times that of the pretreated inorganic carrier, and then add 4-allyl-2-methoxyphenol with a mass 1.2 times that of the pretreated inorganic carrier and 2,2-dimethoxy-2-phenylacetophenone with a mass 0.08 times that of the pretreated inorganic carrier, mix well, and stir to react for 10 hours under ultraviolet light; after the reaction is completed, filter, wash and dry the product components in turn, and finally obtain a compound mildew inhibitor; wherein, the preparation method of the mixed solution is: mix N,N-dimethylformamide and deionized water in a volume ratio of 3:1, and then add 6% of isothiazolinone and 8% of dodecyltrimethylammonium chloride to the obtained mixed solvent, and mix and disperse evenly to obtain a mixed solution.
[0059] The preparation method of the inorganic carrier is as follows: zinc acetate is dissolved in ethylene glycol at a dosage ratio of 50 g / L, and then ammonium acetate 4 times the mass of zinc acetate and sodium citrate 2 times the mass of zinc acetate are added thereto, and after stirring evenly, the obtained mixed components are transferred into a reaction device, and kept warm for reaction at a temperature of 200°C for 20 hours; after the reaction is completed, the reaction product is naturally cooled to room temperature, and after filtering, the filter cake is washed alternately with ethanol and deionized water for 4 times, and then dried to obtain the inorganic carrier.
[0060] Comparative Example 1 is different from Example 1 in that an equal amount of an inorganic carrier is used in this comparative example to replace the compound mildew inhibitor.
[0061] The difference between Comparative Example 2 and Example 1 is that the mixed solution used in this comparative example does not contain isothiazolinone.
[0062] Comparative Example 3 is different from Example 1 in that the mixed solution used in this comparative example does not contain dodecyltrimethylammonium chloride.
[0063] Performance test: The relevant properties of the nanocellulose glass mildew-proof paper samples provided in Examples 1 to 3 and Comparative Examples 1 to 3 were tested respectively, and the test data obtained were recorded in the following table:
[0064]
[0065] By comparing and analyzing the relevant data in the table, it can be seen that the nanocellulose glass mildew-proof paper prepared by the present invention not only has good mildew-proof performance, but also has excellent waterproof performance, which prolongs its service life to a certain extent while also ensuring its quality. This shows that the nanocellulose glass mildew-proof paper and its production process provided by the present invention have a broader market prospect and are more suitable for promotion.
[0066] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0067] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A production process of nanocellulose glass mildew-proof paper, characterized in that: The following steps are involved: The first step is to perform pulping treatment on bleached coniferous wood pulp and bleached broadleaf wood pulp respectively, and then, according to the absolute dry weight percentage, 30-50% of bleached coniferous wood pulp and 50-70% of bleached broadleaf wood pulp are mixed evenly, and the composite wood pulp is pre-acidified for 20-30 minutes; after the acidification is completed, the pH of the composite wood pulp is adjusted to 5.5-6.0 to obtain a mixed pulp; wherein the beating degree of the bleached coniferous wood pulp and the bleached broadleaf wood pulp are both 40-60°SR; The second step is to sequentially add the modified nanocellulose aqueous dispersion, compound mildewproof agent, sizing agent and retention aid to the mixed slurry, mix and stir evenly, and then put it on the net to make a wet paper web, and then squeeze and dehydrate the wet paper web by continuous light pressing to ensure that the dryness of the paper is 35-45%; wherein the concentration of the modified nanocellulose in the modified nanocellulose aqueous dispersion is 3-5wt%; and its dosage is 10-20% of the volume of the mixed slurry; Step 3: Dry the paper obtained after pressing and dehydration at a temperature of 105-110°C. After drying, press 2-6 g / m 2 A waterproof coating is applied on the surface with a coating amount of , and then the nanocellulose glass mildew-proof paper is obtained after secondary drying, calendering, static elimination and winding treatment.
2. The production process of a nanocellulose glass mildew-proof paper according to claim 1, characterized in that: The preparation method of the composite mildew inhibitor comprises the following steps: Step 1, ultrasonically disperse the inorganic carrier in an ethanol aqueous solution with a volume concentration of 70-85% at a solid-liquid ratio of 30-80 g / L, then add a silane coupling agent with a volume of 5-10% of the ethanol aqueous solution, and stir the reaction at a temperature of 50-65° C. for 5-8 hours after ultrasonic dispersion for 10-20 minutes; after the reaction is completed, the resulting components are sequentially subjected to solid-liquid separation, alcohol washing and vacuum drying to obtain a pretreated inorganic carrier; Step 2: ultrasonically disperse the pretreated inorganic carrier in a mixed solution with a mass of 5 to 10 times that of the pretreated inorganic carrier, and then add 4-allyl-2-methoxyphenol with a mass of 0.8 to 1.2 times that of the pretreated inorganic carrier and 2,2-dimethoxy-2-phenylacetophenone with a mass of 0.05 to 0.08 times that of the pretreated inorganic carrier. After mixing evenly, stir and react under ultraviolet light for 6 to 10 hours. After the reaction is completed, filter, wash and dry the product components in turn, and the final product is a compound mildew inhibitor.
3. The production process of a nanocellulose glass mildew-proof paper according to claim 2, characterized in that: The preparation method of the inorganic carrier is as follows: zinc acetate is dissolved in ethylene glycol at a dosage ratio of 20 to 50 g / L, and then ammonium acetate with a mass of 2 to 4 times that of zinc acetate and sodium citrate with a mass of 1 to 2 times that of zinc acetate are added thereto, and after being stirred evenly, the obtained mixed components are transferred into a reaction device, and kept warm for reaction at a temperature of 170 to 200° C. for 15 to 20 hours; after the reaction is completed, the reaction product is naturally cooled to room temperature, and after filtering, the filter cake is washed alternately with ethanol and deionized water for 3 to 4 times, and then dried to obtain the inorganic carrier.
4. The production process of a nanocellulose glass mildew-proof paper according to claim 2, characterized in that: The preparation method of the mixed solution is: N, N-dimethylformamide and deionized water are mixed in a volume ratio of 2 to 3:1, and then 3 to 6% by mass of isothiazolinone and 5 to 8% by mass of dodecyltrimethylammonium chloride are added to the obtained mixed solvent, and the mixed solution is obtained after mixing and dispersing evenly.
5. The production process of the nanocellulose glass mildew-proof paper according to claim 2, characterized in that: The silane coupling agent is selected from any one of 2-mercaptopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 2-mercaptopropyltriethoxysilane and 3-mercaptopropyltriethoxysilane.
6. The production process of a nanocellulose glass mildew-proof paper according to claim 1, characterized in that: The preparation method of the modified nanocellulose is as follows: adding nanocellulose at a dosage ratio of 0.02 to 0.05 g / mL into a 70 to 80 wt% ethanol aqueous solution, adding methyltrimethoxysilane with a mass of 0.3 to 0.4 times that of the nanocellulose after ultrasonic dispersion, mixing and stirring evenly, and then standing for reaction for 3 to 5 hours; after the reaction is completed, filtering and drying the reaction products in turn, and the obtained product is the modified nanocellulose.
7. The production process of the nanocellulose glass mildew-proof paper according to claim 1, characterized in that: The sizing agent is selected from any one of oxidized starch, polyvinyl alcohol and vinyl acetate maleic anhydride copolymer, and its usage is 2-4% of the dry weight of the paper.
8. The production process of the nanocellulose glass mildew-proof paper according to claim 1, characterized in that: The retention aid is selected from any one of melamine formaldehyde resin, propylene oxide or cationic starch, and its usage is 0.8-2% of the dry weight of the paper.
9. The production process of the nanocellulose glass mildew-proof paper according to claim 1, characterized in that: The waterproof coating is composed of the following raw materials in parts by weight: 40 to 50 parts of polyurethane resin emulsion, 25 to 35 parts of acrylic resin emulsion, 10 to 15 parts of zirconium phosphate, 8 to 12 parts of mica powder, 2 to 3 parts of polyoxyethylene polyoxypropylene pentaerythritol ether, 3 to 5 parts of nano cerium oxide, 2 to 3 parts of propylene glycol methyl ether acetate and 1.5 to 2.5 parts of dispersant.
10. A nanocellulose glass mildew-proof paper, characterized in that: The nanocellulose glass mildew-proof paper is prepared by the production process of any one of claims 1 to 9.
Citation Information
Patent Citations
Glass spacing paper and preparation method thereof
CN114086428A